Pengembangan UI/UX Sistem Informasi Alumni SILUNI sebagai Solusi Keterhubungan Alumni SMK - Aftina Ni’ma Rosyada; Arvieka Sabilla Putri Setiadi; Imron Ali Wafi; Lutfia Santika Dewi; Siti Malikha (PT. Hasba Edukasi Mandiri, 2025)
This study aims to develop a web-based alumni information system prototype (SILUNI) integrated with the official website of SMKN 6 Malang. The development was initiated due to the low participation of alumni in tracer studies and limited access to job vacancies, Ausbildung programs, and certification training. The Agile approach was applied through iterative sprints involving end-users, including alumni and the Career Center (BKK). SILUNI's main features include online tracer studies, job vacancy updates, and professional development programs. The system is designed to be responsive and user-friendly, allowing alumni to access information through a centralized platform. The development results indicate that SILUNI has the potential to improve the efficiency of alumni data collection and strengthen the school's role in facilitating graduate career growth. This system is expected to become a strategic solution to foster sustainable relationships between schools and their alumni, supporting industry-relevant program planning.